Fracture of Cylindrical Shells Subjected to Internal Explosion: Numerical Simulation. (2015) - Du, Y.; Ma, L.; Zheng, J.Y.
Abstract: Coupled analysis of explosion-driven fracture is a challenging task due to complicated fluid-structure interactions (FSI) and local large deformations. In this paper, a coupled Finite Element Method-Smoothed Particle Hydrodynamics (FEM-SPH) method was proposed to simulate the fracture of cylindrical shell subjected to internal explosion. The cylindrical shell was modeled by FEM and the movement of detonation products was modeled by SPH, where they were coupled by penalty contact algorithm. A rate-dependent failure criterion for steels at high strain rate conditions was employed in the simulation, which was presented and verified in our previous work. Results showed the interaction between blast wave and cylindrical shell, the dynamic crack propagation and the finial fracture morphology of cylindrical shell. The decoupled analysis was also conducted to make a comparison. It is found the coupled FEM-SPH method can well handle the complicated FSI problem which including local large deformations and ruptures. Compared with decoupled analysis, the fracture of coupled FEM-SPH analysis shows a better agreement with experimental results. In addition, though the over-predicted explosive loads in decoupled analysis cause a severer bulging deformation of cylindrical shell, but the finial fracture is smaller than that of coupled FEM-SPH analysis.